2021
DOI: 10.1002/humu.24220
|View full text |Cite
|
Sign up to set email alerts
|

Genetic pleiotropy of ERCC6 loss‐of‐function and deleterious missense variants links retinal dystrophy, arrhythmia, and immunodeficiency in diverse ancestries

Abstract: Biobanks with exomes linked to electronic health records (EHRs) enable the study of genetic pleiotropy between rare variants and seemingly disparate diseases. We performed robust clinical phenotyping of rare, putatively deleterious variants (lossof-function [LoF] and deleterious missense variants) in ERCC6, a gene implicated in inherited retinal disease. We analyzed 213,084 exomes, along with a targeted set of retinal, cardiac, and immune phenotypes from two large-scale EHR-linked biobanks.In the primary anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…To investigate this, we ascertained whether the CD36 gene family is associated with human Lyme disease using the electronic health record-linked biobank Bio Me (Fig. 4A) ( 46 ). CD36 was less genetically constrained compared to the other family members SCARB1 (SR-BI) or SCARB2 (LIMP-2) according to the Genome Aggregation Database (gnomAD) (table S3) ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate this, we ascertained whether the CD36 gene family is associated with human Lyme disease using the electronic health record-linked biobank Bio Me (Fig. 4A) ( 46 ). CD36 was less genetically constrained compared to the other family members SCARB1 (SR-BI) or SCARB2 (LIMP-2) according to the Genome Aggregation Database (gnomAD) (table S3) ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Biobank data revealed that individuals with rare CD36 LoF variants have higher prevalence of Lyme disease regardless of the genetic diversity and variability among a large population in Bio Me ( 46 ). Our findings were achieved despite the multifactorial and polygenic nature of immune traits ( 57 ) and distinctive non-heritable factors, such as physical activity, prior infections, diet, vaccination status and psychosocial stress ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…This allows it to control the choice of DSB repair pathways, boosting HR while suppressing NHEJ [ 178 , 179 , 181 , 182 ]. Defects in the ERCC6 gene are known to be associated with a variety of diseases, such as Cockayne Syndrome B, retinal dystrophies, arrhythmia and immunodeficiencies [ 183 185 ]. Additionally, studies have documented cases of CSB-PGBD3 fusion gene mutations leading to POI prior to reports of simple ERCC6 mutations that cause POI.…”
Section: Poi Causing Genesmentioning
confidence: 99%
“…Participants with hypertension were identified by the presence of a corresponding ICD-10 diagnosis code, elevated systolic or diastolic blood pressure readings, or documented medications for the treatment of hypertension. 16 We tested for underdiagnosis of HF associated with snLVEF in BioMe based on manual review of physician notes 17,18 in the EHR (unavailable in the UK Biobank) for individuals lacking a diagnosis of HF. Both ICD-10 codes and physician notes in the EHR of BioMe were reviewed while blinded to LVEF status to detect common HF symptoms, including dyspnoea, exertional dyspnoea, peripheral oedema, and fatigue (online supplementary Table S2).…”
Section: Clinical Outcomes and Phenotypesmentioning
confidence: 99%